World Investment Report 2018 - United Nations Conference on Trade; Development (United Nations, 2018)
This report presents international investment trends and prospects at global, regional and national levels, as well as the evolution of international production and global value chains. It analyses the latest developments in new policy measures for investment promotion, facilitation and regulation around the world, as well as updates on investment treaties, their reform and investment dispute settlement cases. It provides an overview of industrial policy models for countries at different development levels and the role of investment policies within each model. It analyses the investment policy implications of the new industrial revolution for high-, middle- and low-income countries and offers a toolkit for investment policymakers on how to use investment policies for new industrial development strategies.